Micropropagation of Superior Clones of Mahogany (Swietenia macrophylla King) from Nodal Segments - Rojas-Vargas, Alejandra (2019)
Mahogany is the most economically important native forest species in Latin America. It is listed in Appendix II of CITES because it has a high exploitation rate due to decades of high extraction rates. The objective of this research was to develop a protocol for the in vitro establishment of two clones (33 and 80), that belong to a forest genetic improvement program. Nodal segments of clones 83 and 33 were established under in vitro conditions using 15 % calcium hypochlorite with an exposure time of 20 minutes. The best culture medium for in vitro establishment of the nodes was MS supplemented with 3% sucrose, 0.016 g/L of agrimycin and benlate, whose use resulted in establishment in 55% of nodes after 16 days of culture. In both clones, the effect of five concentrations of 6-Benzylaminopurine (6-BAP) (0.0, 0.44, 0.88, 1.33, 1.77, and 2.21 μM L-1) on sprouting was evaluated. On average, one sprout per explant was obtained in the 5 treatments evaluated. No significant statistical differences were observed.